MEMS hydrogen gas sensor for in-situ monitoring of hydrogen gas in transformer oil - Kondalkar, Vijay V.; Park, Jihoon; Lee, Keekeun (Sensors and Actuators, B: Chemical, 2021)
Dissolved hydrogen gas analysis (DHGA) is a key aspect that defines the operational status of a transformer and is vital to the maintenance of safety standards in the power grid. In this report, we proposed, MEMS gas sensor arrays for DHGA with a specially designed system having a Wheatstone bridge circuitry with two pairs of resistors. The optimal temperature of the sensor was controlled using a monolithically integrated in-plane microheater and a temperature sensor to monitor the temperature change in the oil and to compensate for the temperature variations in resultant hydrogen sensor signals. The fabricated sensor in a transformer oil showed excellent H2 response (ΔVout = 62μV to 10 ppm and 4.71 mV to 2000 ppm). In addition, long-term stability of sensor performance was observed, confirming that the Al2O3 passivation layer and packaging were effective to enhance the robustness of the sensor in an oil environment. A customized, compact, and portable sensor interface electronics was developed and applied to the sensor system. The results obtained with the developed sensor interface were very similar to those measured with a digital multimeter. Our results demonstrate that the developed sensor system and packaging are very promising for long term monitoring of the operational status of transformers.
Keywords: Digital multimeters; Hydrogen gas sensors; In- situ monitoring; Long term monitoring; Long term stability; Monolithically integrated; Optimal temperature; Temperature variation; Al2O3 passivation layer; Dissolved gas analysis; Hydrogen gas sensor; Transformer insulation oil; Wheatstone bridge